Fleet elements - Williams, Walter Jon (Williams, Walter Jon. Praxis, 2020)
The Praxis, the empire of now extinct Shaa, has again fallen into civil war, with desperate and outnumbered humans battling several alien species for survival. Leading the human forces are star-crossed lovers Gareth Martinez and Caroline Sula, who must find a way to overcome their own thorny personal history to defeat the aliens and assure humanity's survival.